Jeneralochu : dam yafasasawena yaltasakaw yaGenbot 8 qan 1981 a.me. watadarawi yamafanqela mange|st mukara - Eyob Abate Endale ([Addis Ababa : s.n., 2002)
An insider's account of events surrounding the unsuccessful coup against Mengistu's regime in 1989 by his senior army generals.
Includes bibliographical references (p. 302)
In Amharic.